2020
DOI: 10.1155/2020/5204927
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognition in Rehabilitation Context: Different Evolution of Affective and Cognitive Theory of Mind in Mild Cognitive Impairment

Abstract: Maintaining social skills such as Theory of Mind (ToM) competences is important to counteract the conversion into dementia in Mild Cognitive Impairment (MCI). Multidimensional nonpharmacological interventions demonstrated their potential in improving cognitive and behavioral abilities; however, little is known about the long-term effect of such interventions on social skills in people with MCI. The aim of this longitudinal study was to monitor ToM competences considering both cognitive and affective domains in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…The other seven cognitive domains and corresponding scores were visuospatial and executive function for 5 points, language ability for 3 points, attention for 6 points, orientation for 6 points, delayed memory for 5 points, naming for 3 points, and abstract ability for 2 points ( Nasreddine et al, 2005 ). Moreover, existing studies have shown that the scores of different cognitive domains of MoCA assessment result may represent the different cognitive function ( Faria et al, 2020 ; Rossetto et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The other seven cognitive domains and corresponding scores were visuospatial and executive function for 5 points, language ability for 3 points, attention for 6 points, orientation for 6 points, delayed memory for 5 points, naming for 3 points, and abstract ability for 2 points ( Nasreddine et al, 2005 ). Moreover, existing studies have shown that the scores of different cognitive domains of MoCA assessment result may represent the different cognitive function ( Faria et al, 2020 ; Rossetto et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…First, compared with the original sample, the Italian sample is smaller and does not involve clinical information of the participants. In the future, it will be interesting to test the validity of the MAS also in a clinical sample, in order to compare the Italian data with the original ones (for the relevance of the mentalization in clinical samples see, for example [ 49 , 50 ]. Moreover, in this research the educational level of the sample is different from the original one: to pursue our speculation about cultural differences as a way to interpret the new factors that emerged, it would be desirable to compare a sample similar on this variable.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether our results consisted of a preliminary finding in favor of the bio-behavioral link between cognitive and social processes, and the implication of purely cognitive deficits on social cognitive impairment has to be further investigated, especially with a focus on its neural substrates in a longitudinal perspective. Indeed, a significant insight derives from a longitudinal study in a group of patients with mild cognitive impairment ( Rossetto et al. , 2020 ), which demonstrated the association between cognitive ToM performance and changes in the level of cognitive function after rehabilitation, confirming the intrinsic relationship subsisting between ToM limbic–paralimbic and execution loop networks and suggesting the beneficial effect of cross-talk between the specific and supportive ToM circuits.…”
Section: Discussionmentioning
confidence: 98%